Limit Analysis and Shakedown in Plane Frames and Plane Stress Problems - Douglas, Andrew Sholto (Department of Civil Engineering, 2014)
A method is developed for the determination of the shakedown load factor for elastic, perfectly plastic plane frames subjected to cyclic loading or random loads varying between fixed limits. The essential feature of the method is the employment of an automatic force method of elastic analysis which provides self-stress systems for the frame. This in turn permits the ready formulation of the compatibility requirements which are imposed on plastic hinge rotations. As a result, the analysis proceeds with data input which is comparable to straightforward kinematic analysis. A preliminary study of the generalisation of this approach to the limit analysis of plane stress problems is also given.